Controllability and stabilizability of linear time-varying distributed hereditary control systems - Henríquez, Hernán R.; Arita, Andréa Cristina Prokopczyk [UNESP] (Wiley, 2014)
This paper is concerned with the controllability and stabilizability problem for control systems described by a time-varyinglinear abstract differential equation with distributed delay in the state variables. An approximate controllability propertyis established, and for periodic systems, the stabilization problem is studied. Assuming that the semigroup of operatorsassociated with the uncontrolled and non delayed equation is compact, and using the characterization of the asymptoticstability in terms of the spectrum of the monodromy operator of the uncontrolled system, it is shown that the approximatecontrollability property is a sufficient condition for the existence of a periodic feedback control law that stabilizes thesystem. The result is extended to include some systems which are asymptotically periodic. Copyright © 2014 John Wiley &Sons, Ltd.
Keywords: Controllability of distributed hereditary control systems; Stabilization of distributed hereditary control systems; Periodic control systems; Retarded functional differential equations